Strengthening the Law on the Construction of High-rise Building That is Beneficial to Support National Development - Michael Sofian Tanuhendrata; Jovita Irawati; Henry Soelistyo Budi (Global Legal Review, 2021)
The number of high-rise buildings in the big cities of Indonesia is increasing along with land being more limited and its prices being very high. Most of these high-rise buildings are in Jakarta and some of them are facing the risk of building failure that may cause business and operation interruption.  These buildings that have been erected and operating need to receive regular maintenance and supervision to ensure the building's condition and safety. Many building owners and managers do not conduct and plan maintenance and supervision properly causing these buildings of being at risk of fire and building structure – mechanical failure / damage. For this reason, rigorous regulations, and its enforcement in building construction and maintenance are needed to ensure that these buildings operate reliably and encourage building owners and facility manager to comply with them properly. Cultivated Penalty and strict sanctions need to be renewed and must be implemented properly by Government bodies and local authority. Building Audit Institute can be formed to assist the central government and local governments (Governor) in carrying out their functions to ensure the safety and security of buildings, including their users. Strengthening existing laws and regulations will greatly assist in law enforcement and certainty for owners, building managers and building users, which in turn will support national development.